Application of the Discovery Learning Model to Increase the Activeness and Learning Outcomes of Class X Students in the Basic Subject of Handling Agricultural Materials at SMKN 3 Takalar - Iin Novianti Nur; Andi Sukainah; Khaidir Rahman (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a classroom action research that aims to increase the activeness and learning outcomes of students in class X APHP SMKN 3 Takalar. The independent variable in this study is the application of the discovery learning model, while the dependent variable is the activity and student learning outcomes in basic subjects handling agricultural products. The population in this study were all students of class X SMKN 3 Takalar who had basic subjects handling agricultural products, while the sample was class X APHP 1 SMKN 3 Takalar. The research data were obtained by observing student activity using an activity observation sheet, and learning outcomes tests in the form of pre-test and post-test. Based on the data analysis, it can be concluded that the application of the discovery learning model can increase the activeness and learning outcomes of class X APHP SMKN 3 Takalar students.